Shifts in Phytoplankton Community Structure Across an Anticyclonic Eddy Revealed From High Spectral Resolution Lidar Scattering Measurements - Schulien, Jennifer A.; Della Penna, Alice; Gaube, Peter; Chase, Alison P.; Haëntjens, Nils; Graff, Jason R.; Hair, Johnathan W.; Hostetler, Chris A.; Scarino, Amy Jo; Boss, Emmanuel S.; Karp-Boss, Lee; Behrenfeld, Michael J. (Frontiers in Marine Science, 2020)
Changes in airborne high spectral resolution lidar (HSRL) measurements of scattering, depolarization, and attenuation coincided with a shift in phytoplankton community composition across an anticyclonic eddy in the North Atlantic. We normalized the total depolarization ratio (δ) by the particulate backscattering coefficient (bbp) to account for the covariance in δ and bbp that has been attributed to multiple scattering. A 15% increase in δ/bbp inside the eddy coincided with decreased phytoplankton biomass and a shift to smaller and more elongated phytoplankton cells. Taxonomic changes (reduced dinoflagellate relative abundance inside the eddy) were also observed. The δ signal is thus potentially most sensitive to changes in phytoplankton shape because neither the observed change in the particle size distribution nor refractive index (assuming average refractive indices) are consistent with previous theoretical modeling results. We additionally calculated chlorophyll-a (Chl) concentrations from measurements of the diffuse light attenuation coefficient (Kd) and divided by bbp to evaluate another optical metric of phytoplankton community composition (Chl:bbp), which decreased by more than a factor of two inside the eddy. This case study demonstrates that the HSRL is able to detect changes in phytoplankton community composition. HSRL measurements reveal complex structures in both the vertical and horizontal distribution of phytoplankton in the mixed layer providing a valuable new tool to support other remote sensing techniques for studying mixed layer dynamics. Our results identify fronts at the periphery of mesoscale eddies as locations of abrupt changes in near-surface optical properties.